The Relationship Between Stress and Dyspepsia Incidents in the Labuang Baji Hospital - Yantimala, Yantimala (Journal of Asian-african Focus in Health, 2023)
Stress can happen Because the demands of life. The prevalence of dyspepsia patients in health services covers 30% of general practitioner services and 50% of gastroenterology specialist services. The results of endoscopy performed on 550 dyspepsia patients in several hospitals in Indonesia from January 2013 to April 2014, found 44.7% of cases of gastritis and duodenitis abnormalities; and 6.5% of cases with gastric ulcers. The aim of the research was to determine the relationship between stress and the incidence of dyspepsia in the Melati Treatment Room, Sayang Rakyat RSU Makassar. of research is observational , analytical , cross sectional design . The research was carried out in the Melati Treatment Room at RSU Sayang Rakyat Makassar from March 23 to April 15 2017. The sample in the research was 35 patients treated at the Melati Treatment Room at RSU Sayang Rakyat Makassar, using accidental sampling technique. The results of the study showed that there was a relationship between stress and the incidence of dyspepsia , with a value of P = 0.003 < 0.05 . It was concluded that the incidence of dyspepsia is closely related to a person's psychological condition, where someone who experiences a disturbed psychological condition or experiences stress is at risk of experiencing dyspepsia . It is recommended that hospitals provide appropriate information to patients about factors that can become cause of dyspepsia.